Karma and punishment : prison chaplaincy in Japan - Lyons, Adam J. (Harvard East Asian monographs ;, 2021)
"This groundbreaking study of prison religion in East Asia introduces a form of chaplaincy rooted in the Buddhist concept of doctrinal admonition rather than Euro-American notions of spiritual care. Based on archival research, fieldwork inside prisons, and interviews with chaplains, it reveals another dimension of Buddhist modernism that developed as Japan's religious organizations carved out a niche as defenders of society by fighting crime. The case of prison chaplaincy shows that despite constitutional commitments to freedom of religion and separation of religion from state, statism remains an enduring feature of mainstream Japanese religious life in the contemporary era"--